MENGUATKAN BUDAYA ORGANISASI BADAN PENGAWAS PEMILIHAN UMUM SEBAGAI KONSOLIDASI INTERNAL UNTUK MENGHADAPI TANTANGAN PEMILU 2024 - Rusliana, Iu (Jurnal Keadilan Pemilu, 2021)
The Elections Supervisory Agency (Bawaslu) is in charge of overseeing general elections. As an organization, it faces a number of internal and external challenges. The purpose of this article is to describe strategies for strengthening organizational culture in order to internally consolidate in order to face the challenges of the 2024 General Election. Internal consolidation in the form of strengthening organizational culture will go well if internal consolidation in the form of institutional task implementation goes well. This study uses a literature review method. The ndings of this study show that the organizational culture values declared by the Elections Supervisory Agency (Bawaslu) can be seen from its vision of becoming a trusted election supervisory agency. The four values that dene his work culture are solidity, integrity, mentality, and professionalism. Efforts to strengthen the organizational culture within Bawaslu can be carried out through the processes of recruiting new members, education, negotiations, instructions, participation, and expert involvement. Other approaches, such as behavioral, cognitive, humanistic, and psychodynamic approaches, can be used to strengthen organizational culture.